2021
DOI: 10.3892/etm.2021.9646
|View full text |Cite
|
Sign up to set email alerts
|

The vasodilatory mechanism of nitric oxide and hydrogen sulfide in the human mesenteric artery in patients with colorectal cancer

Abstract: Recent studies have focused on the role of gasotransmitters in cancer progression and prevention. Therefore, the current study was designed to explore the vasodilator activity of NO and H 2 S in the human mesenteric arteries of patients with colorectal cancer (CRC) via the activation of K + channels. A total of two sets of experiments were established for the current investigation. Blood samples from patients with CRC were obtained to detect serum levels of endocan and malondialdehyde (MDA). The role of K + ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Many studies focused on the synergistical regulation between the two gases (H 2 S and NO) in smooth muscle, vasodilation in animal, and cobalt toxicity and heat tolerance in plant ( Hosoki, Matsuki & Kimura, 1997 ; Liew et al, 2007 ; Ozfidan-Konakci et al, 2020 ; Hassan, Maulood & Salihi, 2021 ), whereas the research on the synergistic effect of the two gas molecules in regulating the antioxidant system of V. alginolyticus was hardly reported. In fact, the results mentioned above showed that there is significant correlation between the antioxidant system and two gas molecules of H 2 S and NO under the antibiotics stress.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focused on the synergistical regulation between the two gases (H 2 S and NO) in smooth muscle, vasodilation in animal, and cobalt toxicity and heat tolerance in plant ( Hosoki, Matsuki & Kimura, 1997 ; Liew et al, 2007 ; Ozfidan-Konakci et al, 2020 ; Hassan, Maulood & Salihi, 2021 ), whereas the research on the synergistic effect of the two gas molecules in regulating the antioxidant system of V. alginolyticus was hardly reported. In fact, the results mentioned above showed that there is significant correlation between the antioxidant system and two gas molecules of H 2 S and NO under the antibiotics stress.…”
Section: Discussionmentioning
confidence: 99%
“…The ischemic tissues of diabetic mice showed reduced phosphorylation of VEGFR, Akt, and ERK proteins and a negative effect on the angiogenic process. When the ischemic limb of diabetic mice was treated with H 2 S, serum levels of VEGF and PDGF were significantly increased with improved wound healing, indicating the involvement of VEGFR signaling in angiogenesis . The H 2 S-mediated VEGF-induced angiogenesis pathway in ischemic limb injury is illustrated in Figure…”
Section: Physiological Role Of H2s In Angiogenesismentioning
confidence: 94%
“…Diabetes-induced ischemic injured mice were treated with H 2 S donor sodium bisulfide, and angiogenic transcription factors were quantitated using real-time PCR and Western blotting. Increased expression of VEGF, EGF, PDGF, HIF 1α, and angiogenic factor receptors was observed in the treated animals, indicating the role of H 2 S in angiogenesis-related complications of diabetes . Although studies have shown the positive regulation of H 2 S on diabetes-impaired angiogenesis, the precise regulatory mechanisms are not well understood.…”
Section: Physiological Role Of H2s In Angiogenesismentioning
confidence: 98%
See 1 more Smart Citation
“…Utilizing gasotransmitters as therapeutic aids is justified by their roles in carcinogenesis, including enhancement of apoptotic stimuli, inhibition of metastasis and inhibition of angiogenesis. Therefore, using them alone or in combination with cytotoxic agents is an essential research platform for researchers and clinicians in cancer therapy ( 6 , 140 142 ).…”
Section: Effectiveness Of Gasotransmitters In Chemotherapeutic Drug T...mentioning
confidence: 99%